Tingkat Motivasi Masyarakat Kecamatan Kampar Untuk Berolahraga Dalam Pandemi Virus Corona - Hafiz, Muhammad; Henjilito, Raffly (INSPIREE: Indonesian Sport Innovation Review, 2021)
The purpose of the study. The purpose of this study was to determine the motivation level of society to sport in the corona virus environment. This type of research is descriptive and qualitative. Materials and methods. The population in this study were the people of Kampar sub-district. this Kampar district has a population of 45.575 people. Sampling in this study using random sampling techniques, namely taking members of the sample randomly from the population. So that the total sample of this study is 50 from Kampar sub-district. The research instrument used through questionnaires. The data analysis technique used is to calculate the percentage of the society level of motivation. Results. Kampar sub-district society to sport in the corona virus environment is included in the value range of 21%-40% or in the low category with a percentage of 37.8%. Conclusions. Based on the results of research in this study, the motivation level of the Kampar sub-district community to exercise in the corona virus environment is in the low category.